Conceptual design of a composite pressure hull. (1st December 2016) - Craven, R.; Graham, D.; Dalzel-Job, J.
Abstract: Composites are an attractive material for pressure hulls because of their high strength and low density. This paper presents a history of composite pressure vessel hull development over the last 50 years and uses the lessons learnt, to develop a composite pressure hull concept for a shallow diving hull, or buoyancy device. This is done by evaluating several concepts modelled using Finite Element Analysis for weight and other criteria. A converged solution is developed and further analysed for sensitivity to geometric imperfections. These imperfections are shown to have a significant effect on the collapse depth of the composite pressure hull. Highlights: Composite pressure hulls offer significant weight savings compared with steel hulls. Sandwich panel construction offers biggest weight savings. Collapse depth sensitivity to imperfection decreases with imperfection size.